Perancangan Buku Ilustrasi Karakter Jajanan Tradisional Khas Surabaya dengan Teknik Vektor Guna Meningkatkan Minat Anak pada Produk Lokal - Swandawidharma, Yohanes Ev; Bahruddin, Muh; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2016)
Traditional snacks currently almost alienated and less attractive to Surabaya residents, especially the children because of the emergence of a wide range of modern snacks. This happens because of  lack of awareness of  local people to appreciate and preserve the genuine products from the area of Surabaya. Traditional snacks including one culture that must be preserved, therefore the purpose of this research is to design book character illustration of traditional snacks Surabaya to improve a child's interest in local products. Traditional snacks are part of the culture of each city in Indonesia where the snacks are. In the midst of modern meal in Surabaya, which serves a variety of selection, Surabaya typical traditional snacks began to be forgotten among the children. From the analysis of these data, obtained keyword "primary" (main). The main concept can also be interpreted as the most prominent of the rival, through the selection of colorful designs that are expected to be more prominent traditional snacks of modern snacks (snack) or other snacks are more popular today. Children disinterest towards local products due to the lack of recognition of traditional snacks to them. Traditional snacks is also a cultural diversity depends on the region of origin. Currently traditional snacks has been a loss of identity or less popular among children. The design of character for each traditional Surabaya’s snack is expected to attract the interest of children on local products, because in their age is still fairly early, they will be more interested in matters it is easy to understand, such as cartoons, drawings of characters, mascot image and so on. Keywords: Illustrated Books, Traditional Snacks Surabaya, Character, Local Heritage, Primary